The Integration of Kohlberg Moral Development Theory with Education Character - Nainggolan, Mary Monalisa; Naibaho, Lamhot (Technium Social Sciences Journal, 2022)
This research aims to know the integration of Kohlberg's moral development theory with education character. It was done at Universitas Kristen Indonesia from January to June 2020. The method used in this research is a library study, in the form of research whose objects are literature works, namely scientific journals, books, articles in the mass media, and statistical data. The literature obtained was used as an alternative to answering research problems written by researchers regarding the religious and moral development of elementary-age children. The result of the study is that the implementation of character education following the conditions of the individual moral development stage is a wise effort that educators can make in the dynamics of character education. So, implementing aspects of moral knowing, moral feeling, and moral behaviour as the essence of character education will be easier if educators understand the position and stage of moral development the student is taking place.